The Shi arrangement and the Ish arrangement - Armstrong, Drew; Rhoades, Brendon (HAL CCSD, 2011)
International audience This paper is about two arrangements of hyperplanes. The first — the Shi arrangement — was introduced by Jian-Yi Shi to describe the Kazhdan-Lusztig cells in the affine Weyl group of type A. The second — the Ish arrangement — was recently defined by the first author who used the two arrangements together to give a new interpretation of the q,t-Catalan numbers of Garsia and Haiman. In the present paper we will define a mysterious "combinatorial symmetry'' between the two arrangements and show that this symmetry preserves a great deal of information. For example, the Shi and Ish arrangements share the same characteristic polynomial, the same numbers of regions, bounded regions, dominant regions, regions with c "ceilings'' and d "degrees of freedom'', etc. Moreover, all of these results hold in the greater generality of "deleted'' Shi and Ish arrangements corresponding to an arbitrary subgraph of the complete graph. Our proofs are based on nice combinatorial labellings of Shi and Ish regions and a new set partition-valued statistic on these regions. Cet article traite de deux arrangements d'hyperplans. Le premier — arrangement Shi — a été introduit par Jian-Yi Shi pour décrire les cellules de Kazhdan-Lusztig du groupe de Weyl affine de type A. Le deuxième — arrangement Ish — a été récemment défini par le premier auteur pour donner une nouvelle interprétation des nombres q,t-Catalan de Garsia et Haiman. Ici nous définissons une mystérieuse "symétrie combinatoire" entre les deux arrangements et nous montrons que cette symétrie conserve un grand nombre d'informations. Par exemple, les arrangements Shi et Ish ont le même polynôme caractéristique, le même nombre de régions, de régions bornées, de régions dominantes, de régions avec c "plafonds'' et d "degrés de liberté'', etc. En outre, ces résultats se généralisent aux arrangements Shi et Ish "deleted'' correspondant à un sous-graphe arbitraire du graphe complet. Nos preuves reposent sur des étiquetages combinatoires des régions Shi et Ish, ...